2016
DOI: 10.1038/srep26695
|View full text |Cite
|
Sign up to set email alerts
|

Improved intra-array and interarray normalization of peptide microarray phosphorylation for phosphorylome and kinome profiling by rational selection of relevant spots

Abstract: Massive parallel analysis using array technology has become the mainstay for analysis of genomes and transcriptomes. Analogously, the predominance of phosphorylation as a regulator of cellular metabolism has fostered the development of peptide arrays of kinase consensus substrates that allow the charting of cellular phosphorylation events (often called kinome profiling). However, whereas the bioinformatical framework for expression array analysis is well-developed, no advanced analysis tools are yet available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Our analyses using peptide arrays revealed that the phosphorylation of several peptides could not be validated because these were rendered statistically insignificant. Importantly, it has been noted that because of technical reasons data normalization measures tend to account for the loss of information from nearly 50% to 70% of peptides printed on such arrays (58). Therefore, we normally use quasi-stringent t-testing (p value Ͻ 0.1) in our analyses to limit the bias associated with stringent statistical thresholds (81,82).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analyses using peptide arrays revealed that the phosphorylation of several peptides could not be validated because these were rendered statistically insignificant. Importantly, it has been noted that because of technical reasons data normalization measures tend to account for the loss of information from nearly 50% to 70% of peptides printed on such arrays (58). Therefore, we normally use quasi-stringent t-testing (p value Ͻ 0.1) in our analyses to limit the bias associated with stringent statistical thresholds (81,82).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we normally use quasi-stringent t-testing (p value Ͻ 0.1) in our analyses to limit the bias associated with stringent statistical thresholds (81,82). This method of applying a quasi-stringent t-testing threshold in peptide array analyses has also been described by Scholma et al (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, given that a cellular phenotype is often the reflection of changes in the expression patterns of groups of signaling molecules with common biological functions, identifying a change in a group of these molecules is more biologically meaningful than a change in a single molecule. As importantly, it has been noted that 50–70% of the information from peptide arrays can be lost due to technical reasons during data normalization (Scholma et al 2016 ). The cut-off threshold used for InnateDB pathway analysis was more stringent ( P < 0.05 and FC > ± 1.5), with P -values being generated using the hypergeometric distribution test that confirms—prior to correction for multiple testing—whether a pathway is statistically more over-represented in the uploaded dataset than expected by chance.…”
Section: Methodsmentioning
confidence: 99%
“…These normalization methods are selected from the previous studies used on peptides, proteomics, and other microarray datasets. [ 12 15 16 17 ] These methods are described in the following subsection.…”
Section: Methodsmentioning
confidence: 99%